2017
DOI: 10.1155/2017/9580548
|View full text |Cite
|
Sign up to set email alerts
|

HIV among Female Sex Workers in Five Cities in Burkina Faso: A Cross-Sectional Baseline Survey to Inform HIV/AIDS Programs

Abstract: Background Female sex workers (FSWs) are considered a vulnerable population for HIV infection and a priority for HIV/AIDS response programs. This study aimed to determine HIV prevalence among FSWs in five cities in Burkina Faso. Methods FSWs aged 18 and older were recruited using respondent driven sampling (RDS) in five cities (Ouagadougou, Bobo-Dioulasso, Koudougou, Ouahigouya, and Tenkodogo) in Burkina Faso from 2013 to 2014. HIV testing was performed using the HIV testing national algorithm. We conducted bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Details of the study procedures have been previously reported [5666]. Briefly, the original purposes of these studies were to develop population-based estimates of HIV prevalence and determinants of those living with HIV at the individual, network, community and policy levels.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the study procedures have been previously reported [5666]. Briefly, the original purposes of these studies were to develop population-based estimates of HIV prevalence and determinants of those living with HIV at the individual, network, community and policy levels.…”
Section: Methodsmentioning
confidence: 99%
“…2 In Africa, female sex workers (FSWs) are among the most vulnerable: young, homeless, poor, undereducated, alcohol or drug dependent, victims of physical or sexual violence, and resident in areas of economic or political upheaval. 311 Studies in East Africa confirm high prevalence of HIV and STIs in Uganda 12 and Kenya. 13…”
Section: Introductionmentioning
confidence: 94%
“…Studies in Africa and India have found older FSWs to be more vulnerable to HIV infection owing to their involvement in sex work for longer durations, practice of high-risk behaviour in the face of decreasing client load due to advancing age and to their exposure to a larger numbers of clients over time as compared to younger FSWs. [34][35][36] The presence of an additional income source was also significantly associated with HIV positivity in the study states. An additional income source not only provides FSWs earnings at places where sex work is seasonal or poorly paid, but it may also help women in other work areas earn some extra cash.…”
Section: Discussionmentioning
confidence: 90%